Positive response to edrophonium in patients with neurotoxic envenoming by cobras (Naja naja philippinensis). A placebo-controlled study. - Watt, G; Theakston, R; Hayes, C; Yambao, M; Sangalang, R; Ranoa, C; Alquizalas, E; Warrell, D (1986)
To study the ability of anticholinesterase drugs to reverse the potentially fatal paralytic effects of cobra venom, we conducted a placebo-controlled, double-blind crossover trial of intravenous edrophonium (Tensilon) in 10 adults with neurotoxic envenoming caused by bites of the Philippine cobra (Naja naja philippinensis). There was significantly more improvement in ptosis and endurance of upward gaze after edrophonium than after placebo. Five minutes after injection, the mean difference (+/- SD) in the percentage of the iris that was uncovered was 39 +/- 5.47 (70 vs. 31 percent; P less than 0.01), and the mean difference in the number of seconds of upward gaze was 33.1 +/- 9.29 (39.7 vs. 6.6 seconds; P less than 0.01). The expiratory and inspiratory pressures, forced vital capacity, and ability to cough, speak, and swallow also improved after edrophonium. In both the patients who were studied electromyographically, pretreatment and postplacebo responses were typical of myasthenia gravis and became normal after edrophonium. We conclude that anticholinesterases are beneficial in the management of neurotoxic envenoming by Asian cobras (Naja naja), and we recommended a test of edrophonium in any patient with signs of neurotoxic envenoming after snakebite.